European Responses to Ukraine’s nuclear idiosyncrasies: from Kyiv’s independence to Moscow’s aggression (1991-2022) 1 - Vicente,Adérito (2023)
Abstract From Ukraine’s independence in 1991 to Russia’s full-fledged invasion of Ukrainian territory in 2022, the European Union’s (EU) international involvement in Kyiv’s nuclear status can be cha- racterized from an elusive and marginal common policy in the sphere of nuclear disarmament to an ‘unassuming’ common and coherent non-proliferation policy. During this period, Brussels relied on Washington to take the lead. In this context, my objective is to describe what was and is the role of the EU in Ukraine’s nuclear status. The EU’s involvement (even if marginal) can be analysed into two distinct timeframes. First, I propose to study the role of the EU during the period between the dissolution of the Soviet Union and the complete dismantlement of nuclear weapons in Ukraine after the signature of the so-called Budapest Memorandum. Second, I exa- mine the EU efforts to promote non-proliferation and nuclear disarmament agenda between two critical junctures: 2014 Russia’s covert invasion of eastern Ukraine and 2022 Moscow’s full-fledged invasion of Ukraine territory. In the end, I also scrutinize the effects of these two major events on the current European security and nuclear order.